Outcomes differ between subgroups of patients with low back and leg pain following neural manual therapy: a prospective cohort study - Schäfer, Axel; Hall, Toby; Müller, G.; Briffa, Kathy (Springer, 2011)
The objective is to determine if pain and disability outcomes of patients treated with neural mobilisation differ for sub-classifications of low back and leg pain (LB&LP). Radiating leg pain is a poor prognostic factor for recovery in patients with LBP. To improve outcome, a new pathomechanism-based classification system was proposed: neuropathic sensitization (NS), denervation (D), peripheral nerve sensitization (PNS) and musculoskeletal (M). Seventy-seven patients with unilateral LB&LP were recruited. Following classification, all subjects were treated seven times with neural mobilisation techniques. A successful outcome was defined as achieving a minimal clinically important change in pain intensity (11-point numerical rating scale), physical function (Roland Morris disability questionnaire) and global perceived change (7-point Likert scale: from 1 = “completely recovered” to 7 = “worse than ever”). The proportion of responders was significantly greater in PNS (55.6%) than the other three groups (NS 10%; D 14.3% and M10%). After adjusting for baseline differences, mean magnitude of improvement of the outcome measures were significantly greater in PNS compared to the other groups. Patients classified as PNS have a more favourable prognosis following neural mobilisation compared to the other groups.